2019
DOI: 10.3892/ijo.2019.4791
|View full text |Cite
|
Sign up to set email alerts
|

CDC20 associated with cancer metastasis and novel mushroom‑derived CDC20 inhibitors with antimetastatic activity

Abstract: Aberrant expression of cell division cycle 20 (CDC20) is associated with malignant progression and poor prognosis in various types of cancer. The development of specific CDC20 inhibitors may be a novel strategy for the treatment of cancer with elevated expression of CDC20. The aim of the current study was to elucidate the role of CDC20 in cancer cell invasiveness and to identify novel natural inhibitors of CDC20. The authors found that CDC20 knockdown inhibited the migration of chemoresistant PANC-1 pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 41 publications
2
46
0
Order By: Relevance
“… 62 , 63 CDC20 overexpression is related to progression and poor prognosis in various malignant tumors. 64 67 Thus, it is a potential target in multiple cancer treatments. 68 A recent study found that increased expression of CDC20 is related to HCC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“… 62 , 63 CDC20 overexpression is related to progression and poor prognosis in various malignant tumors. 64 67 Thus, it is a potential target in multiple cancer treatments. 68 A recent study found that increased expression of CDC20 is related to HCC development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al (36), reported that high expression of CDC20 in prostate cancer often indicates a poor prognosis. Moreover, a previous study revealed that CDC20 is associated with tumor metastasis (37); thus, future research should focus on CDC20 target inhibitors to develop new drugs to inhibit tumor metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…CDC20B belong to the cell division cycle 20 (CDC20) family of regulatory proteins that interact with several other proteins at multiple points in the cell cycle and CDC20B is required for nuclear movement prior to anaphase and for chromosome separation (34). It has been reported that aberrant expression of CDC20 is associated with malignant progression and poor prognosis in various types of cancer and it has been shown that CDC20 knockdown inhibits the migration of the chemoresistant PANC-1 pancreatic cancer cells and the metastatic MDA-MB-231 breast cancer cell line (35). Thus, it was suggested that the development of specific CDC20 inhibitors might be a novel strategy for the treatment of cancer with elevated expression of CDC20 (35).…”
Section: Discussionmentioning
confidence: 99%